TI_GERICHTE 17.2018.128 vom 2. April 2019 , Lesioni semplici per aver colpito l'avversario al volto con un pugno - TI Tribunale d'appello (2019)
Lesioni semplici per aver colpito l'avversario al volto con un pugno